2009
DOI: 10.1007/s10765-009-0681-4
|View full text |Cite
|
Sign up to set email alerts
|

Crossover Equation and the Vapor Pressure of Supercooled Water

Abstract: Recently, Fuentevilla and Anisimov have published a scaled parametric equation of state that is universal in terms of theoretical variables and belongs to the three-dimensional Ising-model class of universality. The equation can be used for description and prediction of properties of supercooled water. The main advantage of the scaled equation mentioned above is the possibility to predict some properties of supercooled water below the limit of homogenous nucleation, where it is very difficult to obtain experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…[22], and the isobaric heat capacity was derived from the vapor pressure by means of the Clausius-Clapeyron equation as shown in Ref. [42]. We have verified that the result of the fit in the present temperature range was largely insensitive to the particular empirical extrapolations as discussed in Ref.…”
supporting
confidence: 64%
“…[22], and the isobaric heat capacity was derived from the vapor pressure by means of the Clausius-Clapeyron equation as shown in Ref. [42]. We have verified that the result of the fit in the present temperature range was largely insensitive to the particular empirical extrapolations as discussed in Ref.…”
supporting
confidence: 64%
“…The hypothesized LLCP is located in the deeply supercooled region, the no-man’s land below the temperature of homogeneous nucleation. , ,,, Various potential model studies ,,,, have demonstrated the existence of an LLCP, and Table provides the reported location of the LLCP in the various long-range all-atom models.…”
Section: Liquid–liquid Transitionmentioning
confidence: 99%
“…3 In particular, several authors have made attempts to develop a thermodynamic model for the thermodynamic properties of supercooled water based on the LLCP scenario. [3][4][5][6][7][8] The existence of a liquid-liquid critical point in supercooled water is still being debated, especially in view of some recent simulations. 9,10 The purpose of this article is to demonstrate that a theoretical model based on the presumed existence of a second critical point in water is capable of representing, accurately and consistently, all available experimental thermodynamic property data for supercooled ordinary and heavy water.…”
Section: Introductionmentioning
confidence: 99%